EFEKTIVITAS PENURUNAN NYERI PERSALINAN MELALUI PIJAT PUNGGUNG DI RUMAH SAKIT HARAPAN BUNDA KOTA BATAM - Margianti, Norma Jeepi; Wilujeng, Ayu Rosanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Pain can be reduced using a variety of non-pharmacological and pharmacological approaches. Spinal analgesia, epidural, and mixed spinal epidural are the most adaptable, effective, and least depressing pharmaceutical therapies for the central nervous system. Massage is a gate-control theory application that uses massage techniques to relieve pain by creating pain signals. The goal of this study was to look at how different back massage techniques reduced pain. This study used a pre-experimental method with just one group pretest posttest only, with the goal of determining the effect of back massage on labor pain in the active phase of the first stage of inpartum mothers before and after back massage. Based on the findings of the study, the value of Asymp. Sig. (2-tailed): 0.000 is obtained, with the value Ï < 0.05 rejecting H0 and accepting H1. This indicates that the effectiveness of back massage varies according on the intensity of maternal pain. As a result, there is a difference between before and after back massage on the intensity of maternal pain during the first active phase.